Evaluation of marginal adaptation of CoCrMo metal crowns fabricated by traditional method and computer-aided technologies - Hao-Sheng Chang; Yao-Te Peng; Wei-Lin Hung; Ming-Lun Hsu (Elsevier, 2019)
Background/purpose: The purpose of this study was to evaluate the marginal gaps of dental restorations manufactured using conventional loss wax and casting, computer-aided design/computer-aided manufacturing (CAD/CAM), and 3D printing methods. Materials and methods: A zirconia master die model with an upper right first molar resin crown was prepared as a standardized model. A total of 30 resin master die models were duplicated from this standard model. Simultaneously, 10 CoCrMo metal crowns were individually obtained using the conventional loss wax and casting method (Group A), selective laser sintering (Group B), and CAD/CAM (Group C), respectively. The marginal gaps between the crowns fabricated conventional and digital methods with master die models were calculated using a 3D replica and mapping technique. Results: Statistical analyses revealed there were significant differences in the marginal gaps in the group A with group B and C (p < 0.05). The mean marginal gaps between dental crowns with die models were 76 ± 61 μm, 116 ± 92 μm, and 121 ± 98 μm for groups A, B, and C, respectively. Conclusion: Within the limitations of this study, the marginal gaps were clinical acceptable in conventional and digital techniques. Keywords: Conventional lost wax and casting method, Computer-aided design/computer-aided manufacturing, Direct metal laser sintering, Marginal adaptation